BISON: we're in this together: building a Norwegian community of practice for librarians involved in work related to review articles (Journal of EAHIL, 2023)
Librarians involved in assisting researchers with planning, execution and documentation of systematic literature searches are well aware of the considerable amount of practice required to conduct reliable, transparent, and reproducible literature searches. In addition to building the necessary skills and knowledge, factors such as changes in databases, updates in standards or methodologies, and development of new tools makes it difficult to keep up to date. In response an online community of practice has been established in Norway to serve as a platform for facilitating knowledge sharing in these areas. However, building and maintaining an active community is not an easy task. This article describes the development, the activities, the challenges, and the possible future for the community.